The oxford illustrated history of western philosophy - Kenny, Anthony (Oxford University Press, 1994)
From Socrates to Sartre, philosophy has played a central part in the history of Western civilization. Written for the general reader by a team of distinguished philosophers, this illustrated book charts the growth of Western philosophy from its ancient beginnings to the present day - emphasizing the development of philosophy in its intellectual context. Key concepts, doctrines, and schools of thought from both the Anglo-American and continental traditions are explored in a distinctive, authoritative, and accessible way. There is detailed coverage of the lives and works of all the major thinkers through the ages from Plato, Aristotle, Augustine, Aquinas, Descartes, Kant, Hume, Locke, and Hegel, to recent figures such as Russell and Wittgenstein. Their personalities and ideas are brought to life as the book captures the richness and vitality of philosophy across a wide range of cultures and times. The historical framework is reinforced by maps and a detailed chronological table, and the reference material is completed with an annotated guide to further reading and a full index.